Field Effect Transistors: Ionic‐Liquid Gating of InAs Nanowire‐Based Field‐Effect Transistors (Adv. Funct. Mater. 3/2019). (15th January 2019) - Lieb, Johanna; Demontis, Valeria; Prete, Domenic; Ercolani, Daniele; Zannier, Valentina; Sorba, Lucia; Ono, Shimpei; Beltram, Fabio; Sacépé, Benjamin; Rossella, Francesco
Abstract : In article number1804378, Francesco Rossella and co‐workers describe a single n‐type InAs nanowire, electrically contacted, which is surrounded by an ionic liquid – a neutral ensemble of positive and negative ions, liquid at room temperature. A large metallic electrode forces the positive ions to wrap the nanowire. The resulting electric field induces electron accumulation in the nanowire. The ionic liquid gating outstandingly drives the nanowire based field effect transistor.